Evening aspirin intake results in higher levels of platelet inhibition and a reduction in reticulated platelets - a window of opportunity for patients with cardiovascular disease?. (18th August 2021) - van Diemen, J.J.K.; Madsen, M.C.; Vrancken, P.; de Bie, K.; van der Bom, J.G.; Veen, G.; Bonten, T.N.; Fuijkschot, W.W.; Smulders, Y.M.; Thijs, A.
Abstract: Cardiovascular events occur most frequently in the early morning. Similarly, the release of reticulated platelets (RP) by megakaryocytes has a peak in the late night and early morning. Which aspirin regimen most effectively inhibits platelets during these critical hours is unknown. Hence, the primary objective of this trial was to assess platelet function and RP levels at 8.00 AM, in stable cardiovascular (CVD) patients, during three different aspirin regimens. In this open-label randomized cross-over study subjects were allocated to three sequential aspirin regimens: once-daily (OD) 80 mg morning; OD-evening, and twice-daily (BID) 40 mg. Platelet function was measured at 8.00 AM & 8.00 PM by serum Thromboxane B2 (sTxB2 ) levels, the Platelet Function Analyzer (PFA)-200® Closure Time (CT), Aspirin Reaction Units (ARU, VerifyNow®), and RP levels. In total, 22 patients were included. At 8.00 AM, sTxB2 levels were the lowest after OD-evening in comparison with OD-morning ( p = <0.01), but not in comparison with BID. Furthermore, RP levels were similar at 8.00 AM, but statistically significantly reduced at 8.00 PM after OD-evening ( p = .01) and BID ( p = .02) in comparison with OD-morning. OD-evening aspirin intake results in higher levels of platelet inhibition during early morning hours and results in a reduction of RP levels in the evening. These findings may, if confirmed by larger studies, be relevant to large groups of patients taking aspirin to reduce cardiovascular risk.